Endometrial Cytology as a Method to Improve the Accuracy of Diagnosis of Endometrial Cancer: Case Report and Meta-Analysis - Wang, Qing; Wang, Qi; Zhao, Lanbo; Han, Lu; Sun, Chao; Ma, Sijia; Hou, Huilian; Song, Qing; Li, Qiling (Frontiers in Oncology, 2019)
More and more researchers have reported that the (D&C) or Pipelle had low accuracy, high misdiagnosis and insufficient rate of both sampling methods. Endometrial cytology is often compared with histology and seems to be an efficient method for the diagnosis of endometrial disorders, especially endometrial cancer. We report a case of misdiagnosed endometrial cancer by D&C, but with a positive cytopathological finding. Following that, a meta-analysis including 4179 patients of endometrial diseases with cyto-histopathological results was performed to assess the value of the endometrial cytological method in endometrial cancer diagnosis. The pooled sensitivity and specificity of the cytological method in detecting endometrial atypical hyperplasia or cancer was 0.91(95%CI 0.74–0.97) and 0.96(95% CI 0.90–0.99), respectively. The pooled positive likelihood ratio and negative likelihood ratio were 25.4(95% CI 8.1–80.1) and 0.10(95% CI 0.00–0.30), respectively. The diagnostic odds ratio which usually evaluates the diagnostic test performance reached 260(95% CI 36–1905). While D&C or Pipelle are still practical procedure to evaluate the endometrium, cytological examinations should be utilized as an additional endometrial assessment method.